ENHANCING LEARNING OUTCOMES IN VOCATIONAL ECONOMICS THROUGH COOPERATIVE SCRIPT: A CLASSROOM ACTION RESEARCH - Andreanto Pratama, Muhammad; Prasetiyorini, Pudhak; Mugi Hidayanti, Denok (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the Cooperative Script learning model in improving students’ learning outcomes in Economics at SMK Raudlatul Ulum Ledokombo Jember. Although cooperative learning has been widely investigated, limited attention has been given to how Cooperative Script enhances learning outcomes through collaborative interaction within vocational Economics education, particularly in pesantren-based schools. This study contributes to the current literature by demonstrating that structured reciprocal learning can simultaneously strengthen conceptual understanding and collaborative learning behaviour. Empirical findings further revealed a progressive improvement in students’ mean achievement scores from 66.20 before the intervention to 73.10 in Cycle I and 84.23 in Cycle II. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of two iterative cycles of planning, acting, observing, and reflecting. The research involved 32 eleventh-grade students enrolled in an Economics class at SMK Raudlatul Ulum Ledokombo Jember during the 2025/2026 academic year. Data were collected through classroom observations, semi-structured interviews, field notes, documentation, and achievement tests, and analysed using interactive qualitative analysis supported by descriptive quantitative analysis. The findings demonstrate that Cooperative Script substantially improved both students’ academic achievement and classroom participation. Beyond the increase in learning outcomes, students became more actively engaged in collaborative discussions, demonstrated greater confidence in explaining economic concepts, and assumed stronger responsibility for shared learning. The findings suggest that Cooperative Script provides an effective pedagogical approach for creating student-centred Economics classrooms while simultaneously fostering conceptual understanding, communication skills, and collaborative competence in vocational education.